(untitled) (Journal of Renal and Hepatic Disorders, 2021)
There is minimal information on coronavirus disease 2019 (COVID-19) in developing countries regarding renal transplant recipients (RTRs). This paper aimed to study the clinical profile, immunosuppressive regimen, treatment, and outcomes in an RTR with COVID-19. This retrospective study was conducted in the nephrology department of Sri Aurobindo Medical College & Postgraduate Institute, Indore (MP), India, from April 1, 2020 to December 15, 2020. We studied 15 patients, of which 13 were treated at our hospital and two were treated in OPD. The median age of transplant recipients was 45 (Interquartile range [IQR]: 26–62) years, the majority being males, and recipients presented at a median of 4 (IQR: 0.3–11) years after transplant. The most common comorbidities included hypertension in 14 (94%) and diabetes 3 (20%) patients. The presenting symptoms at presentation were cough (80%), headache (52%), fever (46%), and breathlessness (26%). Clinical severity as per computerized tomography (CT) severity score ranged from mild (20%), moderate (53%), and severe (27%). Strategies to modify immunosuppressants included discontinuation of antimetabolites without changes in calcineurin inhibitors and steroids (100%). Antiviral therapy (Favipiravir and Remdesivir) was associated with better outcomes and reduced hospital stay. Risk factors for mortality included ABO-incompatibility, severity of disease, high Coronavirus Disease 2019 (COVID-19) Reporting and Data System (CO-RADS) score, allograft dysfunction before COVID-19 infection, acute kidney injury, elevated inflammatory markers, and intensive care unit/ventilator requirement. Overall patient mortality was 13.2%. Risk factor for mortality in COVID-19 positive with RTR appears to be ABO-incompatible transplant, having a previous history of rejection, and patient requiring ventilatory support.